Kerjasama Kepolisian Daerah Kalimantan Barat Dan Polis Diraja Malaysia (PDRM) Kontinjen Sarawak Dalam Pemberantasan Kejahatan Transnasional Di Wilayah Perbatasan - Syahrial, Ahmad; Purwono, Andi (Faculty of Social and Political Sciences - Universitas Wahid Hasyim, 2022)
This article presents the international cooperation between Regional Police of West Kalimantan and Polis Diraja Malaysia Kontinjen Sarawak (PDRM) in eradicating transnational crime in the border region. The purpose of this research is to know the reason or the driving factor of Regional Police of West Kalimantan estabilished close cooperation on cross-border crime eradication (transnational crime). Researcher found that cooperation for the eradication of transnational crime effected by increasing cross-border crime in the region of West Kalimantan had threatened the safety and order of society. Descriptive-qualitative research methods are used through library research and interviews (indepth interview). From the results of the analysis using the theory of international cooperation K.J. Holsti there are internal factors and ekternal are (1) to enhance the capacity of law enforcement agencies, (2) avoiding the transfer of the burden and responsibility, (3) meet the needs of the exchange of information and handling in konprehensif, (4) Recognizing that transnational crime is a form of shared security threats, (5) the issue of transnational crime has already threatened the safety and order of society, stability and security of the State, (6) combat entry of transnational crime by road area of the border. Through this partnership, Regional Police of West Kalimantan continue to increase prevention efforts and commitment to the eradication of transnational crime in the region of his authority.